Valproate Inhibits Methamphetamine Induced Hyperactivity via Glycogen Synthase Kinase 3β Signaling in the Nucleus Accumbens Core - Xing, Bo (PLoS One, 2015)
Valproate (VPA) has recently been shown to influence the behavioral effects of psycho-stimulants. Although glycogen synthase kinase 3β (GSK3β) signaling in the nucleus accumbens (NAc) plays a key role in mediating dopamine (DA)-dependent behaviors, there is less direct evidence that how VPA acts on the GSK3β signaling in the functionally distinct sub-regions of the NAc, the NAc core (NAcC) and the NAc shell (NAcSh), during psycho-stimulant-induced hyperactivity. In the present study, we applied locomotion test after acute methamphetamine (MA) (2 mg/kg) injection to identify the locomotor activity of rats received repeated VPA (300 mg/kg) pretreatment. We next measured phosphor-GSK3β at serine 9 and total GSK3β levels in NAcC and NAcSh respectively to determine the relationship between the effect of VPA on MA-induced hyperlocomotor and changes in GSK3β activity. We further investigated whether microinjection of VPA (300 μg/0.5 μl/side, once daily for 7 consecutive days) into NAcC or NAcSh could affect hyperactivity induced by MA. Our data indicated that repeated VPA treatment attenuated MA-induced hyperlocomotor, and the effect was associated with decreased levels of phosphorylated GSK3β at Ser 9 in the NAcC. Moreover, repeated bilateral intra-NAcC, but not intra-NAcSh VPA treatment, significantly attenuated MA-induced hyperactivity. Our results suggested that GSK3β activity in NAcC contributes to the inhibitory effects of VPA on MA-induced hyperactivity.